Analysis of the Influence of Corporate Social Responsibility and Good Corporate Governance on Financial Performance in Food & Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Ari Saputra Surbakti; Noni Ardian; Pipit Buana Sari (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) proxied through the Board of Commissioners, Managerial Ownership, Institutional Ownership, and Audit Committee on financial performance as measured using Return on Assets (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This study uses a causal associative quantitative approach with purposive sampling techniques, so that 14 companies were obtained as a sample with a total of 70 observations. The data analysis technique used was panel data regression with the help of EViews 12 software, where based on the Chow Test and Hausman Test, the best model selected was the Fixed Effect Model (FEM). The results of the study showed that simultaneously all independent variables had a significant effect on ROA. Partially, CSR, Board of Commissioners, and Institutional Ownership have a positive and significant effect on ROA, while Managerial Ownership and Audit Committee have no significant effect on ROA. The Adjusted R-squared value of 64.69% indicates that the model is able to adequately explain the variation in financial performance. The long-term success of a company is largely determined by its ability to manage relationships with all stakeholders in a balanced and sustainable manner.